Toxic Workplace Environment: In Search for the Toxic Behaviours in Organizations with a Research in Healthcare Sector - (:unkn) unknown (LUMEN PUBLISHING HOUSE, 2017)
This study provides information on how to identify a toxic workplace; identifies the types of toxic worker behavior, including abusive supervision and workplace mobbing; discusses how toxic workplaces affect employees at all levels; and describes how toxic workplaces can become hostile work environments. For achieving knowledge about how such kind of behaviors and attitudes are perceived by the employees in the selected organizations, a qualitative study was designed. Following the qualitative research, a research study has been designed as a descriptive cross-sectional study which involved the questionnaire survey for primary data collection and analysis. As a result of both qualitative and quantitative studies, it was observed that types of toxic behaviors included tearing others down, passive aggressive leadership, destructive gossip, devious politics, a lot of negativity, abusive supervision, unfair policies, and aggression. The findings reported that there were two categories of toxic workplace environment named as Behavioral Toxics and Contextual Toxics which consisted four variables of toxic behaviors of coworkers, toxic behaviors of managers, toxic socialstructural factors and toxic climate.
Keywords: Toxic Workplace; Toxic Behaviors; Incivility; Abusive Behaviors; Healthcare Sector; AGGRESSION